Balita Pilipinas Ngayon news program and its coverage of Mindanao - Hermoso, Mae Joy
Our perceptions to different things around us are highly based on what media chooses to show us. Some legal research studies proved that portrayal of Mindanao in print media is highly represented with conflict and war, which affects the perception of people about Mindanao. However as explained in the theory of mediation, that image of reality of Mindanao is just a media reality, a reality that media thinks to be important and chooses to show us. Media reality does not always reflect the true reality of a given subject, it is at most times, influenced by their own agendas on telling people what is important to think about, explained in the agenda-setting theory. This research study is a content analysis of the news program Balita Pilipinas Ngayon on how it portrays Mindanao region to the national public. Balita Pilipinas Ngayon is a new and alternative national news program that airs numerous regional reports every weekdays afternoon. The study particularly aims to identify the kind of news that the news program airs about Mindanao, news treatment and tone. It aims to identify the trend of Mindanao news in the news program through the identified kind of news, treatment and tone. The identified trend is considered to be the image of reality that Balita Pilipinas Ngayon portrays to the national public about Mindanao. From November 10- December 09, 2011, the researcher collected 71 Mindanao news for one whole month and using the Pernia?s coding sheet, classified the data according to their prominence, treatment and tone. The focus category that has the highest frequency is the Crime and Disaster category with 64.79% of all Mindanao news gathered considered to be the most prominent Mindanao news aired in Balita Pilipinas Ngayon. 87.32% of all Mindanao news has neutral treatment, meaning no favorable or less favorable statements were given about the issue addressed and simple treatment- only one aspect of the issue/actor is presented. 81.70% has straightforward tone meaning, news are reported through mere listing of events of an issue provided only with basic information (what, when, where, who and how). From the observed data, the researcher concluded that Balita Pilipinas Ngayon gives high importance to crime news, which they might see as salable news to report in covering the Mindanao region, which may indicate that the agenda of the news program is to portray Mindanao with crime and violent reports. This agenda creates a media reality of Midnanao as crime ? filled region. This media reality then becomes an image of reality of Mindanao to the public viewers, most especially to non-residents watching the news program, which might influence the perception of the public viewers on the image of the region. Despite the fact that Balita Pilipinas Ngayon is an alternative news program which deviated from the other existing news programs in the country, compared to other news programs? portrayal of Mindanao, Balita Pilipinas Ngayon in the same manner, still portrays Mindanao as a crime filled region.